Perencanaan Pembiayaan Kesehatan di Rumah Sakit - Riska Febria Afrila; Marice Simarmata (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Financing in the health sector plays an important role in ensuring the sustainability of hospital operations and the provision of quality health services. Structured and efficient financing planning contributes greatly to improving the health of the community. However, in practice, it is not uncommon to find problems due to weak financial planning, such as budget limitations that have an impact on the low quality of health services and waste due to inappropriate spending. To overcome these problems, strategic steps are needed, including through increasing funding, more accountable management and allocation of funds, and controlling service costs. Thus, the issue of health financing has a significant influence on the quality of public health and is an important part of the development of the national health system.